Alex Rider : Skeleton Key - Book 3 - Horowitz, Anthony; 1955- (New York, 2003)
Reluctant teenage-spy Alex Rider, on a routine mission at the Wimbledon tennis championships, gets caught up in Chinese gangs, illegal nuclear weapons, and the suspect plans of his Russian host, General Sarov.
"An Alex Rider adventure"--Jacket.
Keywords: Spies; Fiction; Tennis; Fiction; Terrorism; Fiction; Orphans; Fiction; England; Fiction